Optimal channel assignment for multi-hop wimax mesh networks - Haleem, Ahmed Shain (2016)
In this work, we study the problem of interference that affects quality of service (QoS) for diverse multimedia services which are the main concerns for WiMAX mesh networks and enhance the scheduling for multi-hop WiMAX mesh networks by assessing the optimal channel assignment. The objective of this study is to guarantee a throughput for individual stream in a multi-hop WiMAX mesh network. We study various scheduling algorithms with respect to the QoS constraints and come up with a framework which would help us to understand the optimal channel assignment and enhance the scheduling in multi-hop WiMAX mesh networks. Our proposed method is able to produce good quality solutions for improving the scheduling scheme of multihop WiMAX mesh networks effectively to achieve QoS guarantees when compared with other QoS standard algorithms.